2017
DOI: 10.4103/ijem.ijem_108_17
|View full text |Cite
|
Sign up to set email alerts
|

Osteoporosis in otherwise healthy patients with type 2 diabetes: A prospective gender based comparative study

Abstract: Background and Objective:Type 2 diabetes mellitus (T2DM) may affect bone loss differentially in adult males and postmenopausal females. We evaluated the prevalence of osteoporosis in otherwise healthy adults with T2DM.Materials and Methods:In a cross-sectional study, adults with T2DM, aged 50 years and above, were evaluated for bone mineral density (BMD) using dual-energy X-ray absorptiometry (DXA) scan at spine and hip. T-score of ≤−2.5 was defined as osteoporosis and score −2.49 to −1.0 as osteopenia at eith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
(28 reference statements)
3
8
0
Order By: Relevance
“…Our study had relatively more osteopenia (47%) patients than osteoporosis (39%) which is in agreement with the observation of Sharma et al 6 who also had higher number of osteopenia (51.5%) patients than osteoporosis (35.5%). They had an overall prevalence of osteopenia and osteoporosis close to ours (87% vs 86% in our study).…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Our study had relatively more osteopenia (47%) patients than osteoporosis (39%) which is in agreement with the observation of Sharma et al 6 who also had higher number of osteopenia (51.5%) patients than osteoporosis (35.5%). They had an overall prevalence of osteopenia and osteoporosis close to ours (87% vs 86% in our study).…”
Section: Resultssupporting
confidence: 93%
“…One of the reasons could be primarily the present study had only few cases with T2DM duration >10 years (mean duration of T2DM 6.21 years). Compared to our study, Prakash et al [6,5] had 35.4% patients with T2DM duration >10 years and also included patients with T2DM duration >15 years. Our study findings are in agreement with the observations of Mobini et al [14] who also did not find a significant association osteoporosis and duration of diabetes.…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…Malnutrition is also very common, with predominantly high carbohydrate diet and low calcium and protein intake. HIV/AIDS is a disease of low-income group in India, and other factors such as loss of employment and depression may contribute to osteoporosis, the prevalence of which was found to be even higher than that reported in patients with rheumatoid arthritis (15%)[ 11 ] or diabetes mellitus (15%)[ 12 ]. We found a significant association of low BMD with longer duration of disease.…”
Section: Discussionmentioning
confidence: 99%
“…A cross-sectional study including 200 subjects in India found that the prevalence of OP in patients with T2DM is about 20-35% [ 6 ]. The risk of hip fracture is 2.5-fold higher than general population in patients with T2DM [ 7 ].…”
Section: Introductionmentioning
confidence: 99%